A Full Computerized Workflow for Planning Surgically Assisted Rapid Palatal Expansion and Orthognathic Surgery in a Skeletal Class III Patient - Orazio Bennici; Alessia Malgioglio; Serena Moschitto; Gianrico Spagnuolo; Alberta Greco Lucchina; Vincenzo Ronsivalle; Gaetano Isola; Antonino Lo Giudice (Case Reports in Dentistry)
In the present case report, we present and discuss the digital workflow involved in the orthodontic/orthognathic combined treatment of a skeletal malocclusion correction in a 17-year-old male patient affected by a skeletal class III, facial asymmetry, sagittal and transversal deficiency of the medium third of the skull, dental crowding, and bilateral cross-bite. The first stage of the treatment involved surgically assisted rapid palatal expansion and occlusal decompensation, using fixed self-ligating appliance. An orthodontic software package (i.e., Dolphin 3D Surgery module) was used to perform virtual treatment objective evaluation by integrating data from cone beam computer tomography acquisition, intraoral scan, and extraoral photographs. The software allowed a comprehensive evaluation of skeletal, dento-alveolar, and soft-tissue disharmonies, qualitative and quantitative simulation of surgical procedure according to skeletal and aesthetic objectives, and, consequently, the treatment of the malocclusion. Using a specific function of the software, the surgical splint was designed according to the pre-programmed skeletal movements, and subsequently, the physical splint was generated with a three-dimensional (3D) printing technology. Once a proper occlusal decompensation was reached, a Le Fort I osteotomy of the maxilla and a bilateral sagittal surgical osteotomy of the mandible were executed to restore proper skeletal relations. The whole treatment time was 8 months. The orthodontic/orthognathic combined treatment allowed to correct the skeletal and the dental imbalance, as well as the improvement of facial aesthetics. Accordingly, the treatment objectives planned in the virtual environment were achieved. Virtual planning offers new possibilities for visualizing the relationship between dental arches and surrounding bone and soft structures in a single virtual 3D model, allowing the specialists to simulate different surgical and orthodontic procedures to achieve the best possible result for the patient and providing an accurate and predictable outcome in the treatment of challenging malocclusions.